Effect of hollow blades on flow improvement in turbines and large scale fans - Najafzadeh A. (2023)
In this paper different computational fluid dynamics (CFD) methods have been defined and modern methods are developed and compared with conventional ones. Numerical methods are used to calculate volume flow rates of turbines and axial flow fans. Validation of results with experimental data is improved significantly by using hollow blades and this will result to increased efficiency of turbines and large scale fans.